Writings about the city and architecture in the Ciudad y Campo y Caminos Magazine 1924-1930 - Delgado Galimberti, Luis (2008)
This paper represents and selection and review of articles relating to architecture and city published in the journal Ciudad, Campo and Caminos, Between 1924 and 1930.